Factors Affecting Cyberbullying In Adolescents: Literature Review - Eni Hidayati; Mariyam Mariyam; Desi Ariyana Rahayu; Mohamad Fatkul Mubin; Ghodiq Ufthoni (Universitas Aisyah Pringsewu, 2022)
One of the challenges that adolescents have to face on the internet is that they are easy to become perpetrators or victims of cyberbullying. Cyberbullying is intimidating behavior that is carried out individually or in groups using electronic media to harass, threaten, or humiliate someone and is done repeatedly. This writing aims to analyze previous research on perpetrators and victims of adolescent cyberbullying. This writing design uses research article searches in several databases with certain keywords in the 2019-2022 period and 20 articles are obtained that meet the inclusion criteria. The results of writing a literature review show that various factors influence cyberbullying behavior that occurs in victims and perpetrators among adolescents, individual factors, namely experience of violence, age, perception, psychological control, gender, and use of addictive substances. The article search method, the conclusion of writing this literature review shows that the factors that trigger cyberbullying behavior that occurs in victims and perpetrators among adolescents are gender, age, peers, and social media. In addition, there are several types of cyberbullying such as outing, cyber stalking, harassment, flaming, denigration, and impersonation. Meanwhile, a good stress-coping strategy for developing self-efficacy for victims of cyberbullying is emotional focus coping. Result: The conclusion of writing this literature review shows that the factors that trigger cyberbullying behavior that occurs in victims and perpetrators among adolescents are gender, age, peers, and social media. In addition, there are several types of cyberbullying such as outing, cyber stalking, harassment, flaming, denigration, and impersonation. Meanwhile, a good stress-coping strategy for developing self-efficacy for victims of cyberbullying is emotional focus coping. The conclusion of this literature review shows that the factors that trigger cyberbullying behavior in victims and perpetrators among adolescents are gender, age, peers, and social media. In addition, there are several types of cyberbullying such as outing, cyber stalking, harassment, flaming, denigration, and impersonation. Meanwhile, a good stress-coping strategy for developing self-efficacy for victims of cyberbullying is emotional focus coping. Astrak: Latar belakang: Salah satu tantangan yang harus dihadapi remaja di internet adalah mudahnya mereka menjadi pelaku atau korban cyberbullying. Cyberbullying adalah perilaku intimidasi yang dilakukan secara individu atau kelompok dengan menggunakan media elektronik dengan tujuan melecehkan, mengancam, mempermalukan seseorang dan dilakukan secara berulang-ulang. Tujuan: Penulisan ini bertujuan untuk menganalisis penelitian terdahulu terkait dengan pelaku dan korban cyberbullying remaja. Perancangan penulisan ini menggunakan pencarian artikel penelitian di beberapa database dengan kata kunci tertentu pada periode 2019-2022 dan didapatkan 20 artikel yang memenuhi kriteria inklusi. Penulisan literature review menunjukkan bahwa terdapat berbagai faktor yang mempengaruhi perilaku cyberbullying yang terjadi pada korban dan pelaku di kalangan remaja, faktor individu yaitu pengalaman kekerasan, usia, persepsi, kontrol psikologis, jenis kelamin, penggunaan zat adiktif. Metode pencarian artikel, kesimpulan dari penulisan literature review ini menunjukkan bahwa faktor-faktor pemicu perilaku cyberbullying yang terjadi pada korban dan pelaku di kalangan remaja adalah jenis kelamin, usia, teman sebaya, dan media sosial. Selain itu, ada beberapa jenis cyberbullying seperti outing, cyberstalking, pelecehan, flaming, fitnah, dan peniruan identitas. Sementara itu, strategi coping stres yang baik untuk mengembangkan efikasi diri bagi korban cyberbullying adalah emotional focus coping. Hasil: Kesimpulan dari penulisan literature review ini menunjukkan bahwa faktor-faktor pemicu perilaku cyberbullying yang terjadi pada korban dan pelaku di kalangan remaja adalah jenis kelamin, usia, teman sebaya, dan media sosial. Selain itu, ada beberapa jenis cyberbullying seperti outing, cyberstalking, pelecehan, flaming, fitnah, dan peniruan identitas. Sementara itu, strategi coping stres yang baik untuk mengembangkan efikasi diri bagi korban cyberbullying adalah emotional focus coping. Kesimpulan dari penulisan literature review ini menunjukkan bahwa faktor pemicu perilaku cyberbullying yang terjadi pada korban dan pelaku di kalangan remaja adalah jenis kelamin, usia, teman sebaya, dan media sosial. Selain itu, ada beberapa jenis cyberbullying seperti outing, cyberstalking, pelecehan, flaming, fitnah, dan peniruan identitas. Sementara itu, strategi coping stres yang baik untuk mengembangkan efikasi diri bagi korban cyberbullying adalah emotional focus coping.